MMP-Activated Fluorescence Imaging Detects Early Joint Inflammation in Collagen-Antibody-Induced Arthritis in CC-Chemokine Receptor-2-Null Mice, In-Vivo - Jessica M. Ibarra; Fabio Jimenez; Hernan G. Martinez; Kassandra Clark; Seema S. Ahuja (Hindawi Limited, 2011)
The Standard measures of experimental arthritis fail to detect, visualize, and quantify early inflammation and disease activity. Here, we describe the use of an injectable MMP-activated fluorescence agent for in vivo quantification of acute inflammation produced by collagen-antibody-induced arthritis (CAIA) in CC chemokine receptor-2 (Ccr2−/−) null mice. Although Ccr2−/− DBA1/J mice were highly susceptible to and rapidly developed CAIA, the standard clinical assessment of fore or hind paw thicknesses was unable to detect significant acute inflammatory changes (days 3-10). Remarkably, noninvasive, in situ, MMP-activatable fluorescent imaging of Ccr2−/− DBA1/J mice with CAIA displayed acute joint pathology in advance of clinically measurable acute inflammation (days 5, 7, and 10). These results were confirmed by the histology of ankle joints, which showed significant inflammation, bone loss, and synovial hyperplasia, compared to control mice at postimmunization day 5. The MMP-mediated fluorescence technique holds tremendous implications for quantifiable examination of arthritis disease activity of acute joint inflammation.